Pengembangan Desain Bentuk Dan Makna Pembuatan Kapal Pinisi Berbasis Kearifan Lokal - Silatul Rahmi; Syamsu A. Kamaruddin; Arlin Adam; Arifuddin Usman (Departement of Mathematics Education, 2024)
Pinisi can be said to be a symbol and symbol of extraordinary technical progress and is still based on high artistic values ​​and traditional culture. Because of the nature of the pinisi boat, it is not only used as a means of transportation or as a means of high value export commodities, but is also something of a symbolic nature. Because of its symbolic nature, in the process of making it as well as in the processes of launching it and its use it is required in traditional ceremonies which are based on belief in a power. By understanding the form and meaning of the Pinisi shipbuilding ritual, efforts can be made to preserve and develop this culture. Apart from that, this research can also provide deeper insight into the local wisdom and unique culture of the Bulukumba people. The distinctive and unique shape of the pinisi ship contains symbols that symbolize strength, courage, beauty and skill. The symbolism in the ritual of making pinisi ships in Bulukumba Regency illustrates the importance of the values ​​of togetherness, cooperation and collaboration in society. Apart from that, the ritual of making pinisi boats also has a symbolic meaning as a form of togetherness, cooperation, hierarchy and obedience to authority in society. Pinisi ships also have